The seal louse (Echinophthirius horridus) in the Dutch Wadden Sea: investigation of vector-borne pathogens - Hirzmann, Jörg; Ebmer, David; Sánchez-Contreras, Guillermo J.; Rubio-García, Ana; Magdowski, Gerd; Gärtner, Ulrich; Taubert, Anja; Hermosilla, Carlos (Parasites & Vectors, 2021)
Background!#!Belonging to the anopluran family Echinophthiriidae, Echinophthirius horridus, the seal louse, has been reported to parasitise a broad range of representatives of phocid seals. So far, only a few studies have focused on the vector function of echinophthiriid lice, and knowledge about their role in pathogen transmission is still scarce. The current study aims to investigate the possible vector role of E. horridus parasitising seals in the Dutch Wadden Sea.!##!Methods!#!E. horridus seal lice were collected from 54 harbour seals (Phoca vitulina) and one grey seal (Halichoerus grypus) during their rehabilitation period at the Sealcentre Pieterburen, The Netherlands. DNA was extracted from pooled seal lice of individual seals for molecular detection of the seal heartworm Acanthocheilonema spirocauda, the rickettsial intracellular bacterium Anaplasma phagocytophilum, and the cell wall-less bacteria Mycoplasma spp. using PCR assays.!##!Results!#!Seal lice from 35% of the harbour seals (19/54) and from the grey seal proved positive for A. spirocauda. The seal heartworm was molecularly characterised and phylogenetically analysed (rDNA, cox1). A nested PCR was developed for the cox1 gene to detect A. spirocauda stages in seal lice. A. phagocytophilum and a Mycoplasma species previously identified from a patient with disseminated 'seal finger' mycoplasmosis were detected for the first time, to our knowledge, in seal lice.!##!Conclusions!#!Our findings support the potential vector role of seal lice in the transmission of A. spirocauda and reveal new insights into the spectrum of pathogens occurring in seal lice. Studies on vector competence of E. horridus, especially for bacterial pathogens, are essentially needed in the future as these pathogens might have detrimental effects on the health of seal populations. Furthermore, studies on the vector role of different echinophthiriid species infecting a wide range of pinniped hosts should be conducted to extend the knowledge of vector-borne pathogens.